Regulation of HbA1c of uncontrolled diabetic type II obese and normal weight patients by oral hygiene performance (Comparative study) - Hadratie, Sana F; Al-Juboury, Abdullatif A H (Journal of Baghdad College of Dentistry, 2013)
Background: The association between periodontal diseases incidence and development and the metabolic diseases as Diabetes Mellitus and Obesity are recently have attract great deal of researchers attention and investigation. The periodontal health proved to reduce the systemic inflammatory reactions and positively improve the glycemic control of diabetes Type2 patients. The aim of the study was to investigate the influence of oral hygiene control on the glycemic control of obese and normal weight moderately controlled Diabetic Type 2 patients, in addition to study the association of obesity with the gingival inflammation.Materials and Methods: Cross sectional study of three months duration. Included 30 moderately controlled diabetic type2 patients who attend the Specialist Center for Endocrine and Diabetes diseases Baghdad Al-Russafa administration / Iraqi Ministry of Health, were grouped into two groups, G1 of normal weight diabetics, and G2 obese diabetics according to their BMI level, the oral hygiene status measured by their PLI,GI,BBOP,PDI,CAL was conducted at each of the five visits of three weeks interval between each till the end of three months duration of the study and the level of their glycemic control measured by HbA1c level was conducted at the first and the fifth visit of the research duration , BMI was measured at the first and the fifth visit also. Paired t-test, ANOVA, Qui-square and Pearson correlation statistical analysis was used to investigate the significance of the improved glycemic control after oral hygiene control (OHC) of both G1 and G2.Results: periodontal parameters of both G1 and G2 were significantly improved after OHC with a significant reduction in HbA1c level of both normal weight and obese patients.Conclusion: The Oral Hygiene Control (OHC) is sufficient to improve reduction in Diabetes control level with or without overweight.OHC home care and professional measures could improve the gain in periodontal health in normal weight diabetics and overweight diabetics Obesity has an association with the presence of bleeding on probing as an indicator of the gingival inflammation in diabetic Type2 patients.